Review of drug recalls and quality of pharmaceutical products in Nepal - Astha Neupane; Maheshwor Bastakoti; Sabita Tamang; Basant Giri (BMJ Open)
Objectives To evaluate the pattern of substandard and falsified pharmaceutical products recall in Nepal.Setting We analysed drug recall notices issued by the Department of Drug Administration (DDA), Nepal, and systematically reviewed peer-reviewed research articles during January 2010 to December 2020.Participants This study did not include human participants. However, data were collected from 72 drug recall notices issued by DDA and four research papers.Results A total of 346 pharmaceutical products were recalled during the reported period. The number of recalled pharmaceutical products has increased significantly over the past decade in Nepal. The most frequently recalled drugs were antimicrobials followed by gastrointestinal medicines, vitamins and supplements and pain and palliative medicines among others. Number of imported recalled drugs were slightly higher (42.2%) than domestic recalled drugs (40.7%). Sixty-two percentage of recalled drugs were substandard, 11% were falsified and remaining 27% were not registered at the DDA. Similarly, higher number of modern drugs (62%) were recalled than traditional ones (35%). Hand sanitisers used to minimise COVID-19 transmission contributed significantly to the list of recalled pharmaceutical products in 2020. Most of these sanitisers contained significant amounts of methanol (as high as 75% v/v) instead of appropriate amount of ethyl or isopropyl alcohol. The peer-reviewed research papers reported issues with labelling, unregistered drugs and drugs failed in several laboratory testing.Conclusion Our analysis showed that number of recalls of substandard and falsified drugs are increasing in Nepal. Since the recall data in this paper did not include number of samples tested and location of samples collected, more studies to understand the prevalence of substandard and falsified drugs in Nepal is recommended.